Malaysian communications and multimedia commission's powers in regulating online publication: the case of publication in public internet - Shuaib, Farid Sufian (s.n, 2012)
Malaysia Communications and Multimedia Commission (MCMC) is a body established under the Malaysian Communications and Multimedia Commission Act 1988, among others, to regulate all matters relating to communications and multimedia activities. Since it has a central role in regulating the internet, there is a need to examine the extent of power of the MCMC in regulating online publication particularly publication that has public interest character. This is because the independence of such a regulatory commission in law and in operation may be relevant if such publication is in the interest of the public but not in the interest of parties in power